PSV-12 Impact of grain processing and undegradable fiber on chewing behavior and feed sorting of finishing beef cattle. (30th November 2020) - Ran, Tao; Saleem, A M; Beauchemin, Karen; Penner, G; Yang, Wenzhu
Abstract: The objective was to investigate the effects of processing index (PI, weight after processing/weight before processing × 100) of barley grain and dietary undegradable fiber (uNDF, 240 h of incubation in rumen) concentration on chewing behavior (3 days, video recording) and feed sorting of finishing beef cattle. Six ruminally cannulated beef heifers (BW=715 kg) were used in a 6 × 6 Latin square design with 3 PI (65, 75 and 85%; fine, medium, coarse, respectively) × 2 uNDF concentrations (low and high; 4.6 vs. 5.6% of DM) factorial arrangement. Heifers were fed ad libitum a TMR consisting of 10% barley silage (low uNDF) or 5% silage and 5% chopped straw (high uNDF), 87% dry-rolled barley grain, and 3% vitamin and mineral supplement. An interaction of PI with uNDF occurred (P < 0.01) for DM intake, ruminating and total chewing time. Intake of DM (kg/d) did not differ (12.1) between low and high uNDF diets with 65 or 75% PI, whereas it was greater (P < 0.05) for high (12.7) than low (12.1) uNDF diets with 85% PI. Eating time (min/d) was not affected by PI but eating time (106 vs. 95 min/d; P = 0.03) and eating index (9.3 vs. 8.0 min/kg DM; P = 0.02) were greater with high than low uNDF diets. Ruminating (305 vs. 258 min/d) and total chewing (406 vs. 357 min/d) times were greater (P < 0.05) with high than low uNDF at 65% PI, with no effect of uNDF at 75 and 85% PI. Moreover, no interaction between PI and uNDF and no effect of PI on sorting index was observed. Heifers fed high vs. low uNDF diets sorted (P < 0.01) against long particles (>19 mm). These results suggest that when cattle are fed finely processed barley, increasing uNDF concentration of the diet may promote chewing and benefit rumen health.